A corporação médica brasileira e seu projeto formativo - Tuzzin, Leandro (2023)
This Thesis focuses on the medical corporation in Brazil. The term "corporation," within the scope of this work, denotes the exercise of power that seeks to legitimize the medical profession in society and assert it before the State. It claims social prestige, favors from the government, constantly improved remuneration, and increasingly extensive privileges for its members. Moreover, it goes beyond that: it delimits and defends the realm of its activities, circumscribes the qualified professional for the practice of medicine, controls their education, their entry into the corporation, and the performance of their activities. At its extreme, the corporation aspires to be a state within the State; ultimately, its purposes aim to encase the State, to hover above it, and to use it for the prioritized fulfillment of its interests. The Brazilian medical corporation has a history. It slowly reveals and becomes explicit, step by step, until it reaches maturity, when it shows all its power and splendor, generates its own contradictions, and ages (loses alignment with the new times, diminishes its protagonism in the correlation of social and institutional forces), exposing its cracks and limits. The history of the medical corporation will be addressed as follows: the first chapter discusses the long period of its impossibility (Colonial Brazil) and the period of its anticipation (Imperial Brazil and the Old Republic); the second chapter explores its full establishment (Vargas Era) and exercise of its maximum power (Military Regime); the third chapter examines the period of its contradictions and weakening (New Republic). The conclusion highlights six contradictions experienced by the corporation and assesses future possibilities. The first contradiction juxtaposes the ideal of the medical profession as a liberal art, a "calling," and a vocation aimed at saving people with the pragmatic schemes of mercantilism that subject everything to the pursuit of financial advantages. The second contradiction concerns the principle of the personal nature of medical acts (according to the Medical Code of Ethics), which clashes with the consumer relationship and the judicialization of medical errors based on the Consumer Protection Code. The third contradiction relates to the medical corporation's stance towards the state, which initially sought the favors of the government during its formation and consolidation but later vehemently opposed key public health policies. The fourth contradiction arose at the end of the Military Dictatorship, manifested in the conflict between conservative sectors of the medical profession, bound by corporate interests, and progressive sectors that, in tune with political and civil movements, advocate for a public and universal healthcare system (SUS). The fifth contradiction once again confronts the profession as a liberal art with the institutionalization of medical practice. The final contradiction opposes the perspectives of the medical corporation in the educational field with the interests and power of large educational conglomerates, which are increasingly influential in the country.